ASYMBIOTIC SEED GERMINATION OF AN ANTICANCEROUS TERRESTRIAL ORCHID Eulophia nuda Lindl. AND ITS ADULTERANT Geodorum densiflorum (Lam) Schltr. (Applied Biological Research, 2024)
Eulophia nuda Lindl. corms are used to cure cancer and is overexploited by the   traditional medicine practitioners and medicinal plant traders. The corms of   Geodorum densiflorum look morphologically similar to the corms of Eulophia   nuda, hence it is used as an adulterant to the corms of Eulophia nuda,   consequetly, the population of G. densiflorum is also facing the exploitation   pressure. In present study, asymbiotic seed germination of both the terrestrial   orchids was achieved using six media like Vacin and Went (WV) medium,   Malmgren modified (MM) terrestrial orchid medium, modified Kundson C  medium, ½ MS medium, Lindemann medium (LM) and BM1 medium along   with three photoperiods (0/24, 16/8, and 24/0 h L/D). Eulophia nuda showed   highest asymbiotic seed germination on MM medium (80.55 %) and the best   light treatment was 0/24 h L/D. The highest asymbiotic seed germination of G densiflorum was on VW (84.07%), LM (83.29%) and BM 1(81.02%) and the best   light treatment was 24/0 h L/D.
Keywords: Adulteration; anticancer properties; asymbiotic seed germination; Eulophia; Geodorum; Ex situ conservation